PENGARUH TOTAL ASSETS TURNOVER DAN RETURN ON ASSETS TERHADAP PERTUMBUHAN LABA - Purwanti, Arni; Puspitasari, Intan (Jurnal Riset Akuntansi, 2019)
ABSTRACT The research was purpose to find out how much influence total assets turnover on profit growth and how much influence return on assets on profit growth in sub sector food and beverage company listed on the Indonesia Stock Exchange. The research was purpose to find out how much influence total assets turnover and return on assets effect on profit growth. The method used in this research is descriptive method verification with quantitative approach. The sampling method in this study using nonprobability sampling with purposive sampling approach. The unit of analysis in this research is the company's annual financial report taken in 2011-2015. The data were analyzed using multiple linear regression. Testing the hypothesis in this study using the statistical t-test statistic with SPSS 20.0 for Windows. Results from this study showed that total assets turnover and return on assets effect on profit growth in sub sector food and beverage company listed in Indonesia Stock Exchange. The results of this study also showed that total assets turnover and return on assets influence profit growth in sub sector food and beverage company listed in Indonesia Stock Exchange. Keywords : Total Assets Turnover, Return On Assets, Profit Growth